Drying Characteristics of Pine Wood (Pinus merkusii Jungh. et de Vriese) Using Hot Air, Infrared, and Combined Infrared-Hot Air - Yefri Chan; Dwi Aries Himawanto; Budi Kristiawan; Indri Yaningsih; Erwin Erwin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This research aims to determine the drying characteristics of Merkusii pine wood (Pinus merkusii Jungh. et de Vriese) using three methods, including the hot air drying, infrared, and combined infrared-hot air. The drying characteristics included temperature distribution, reduction in moisture content, drying rate, wood surface temperature distribution, and specific energy consumption (SEC). The results show that the combined infrared-hot air drying method produces a faster drying time and the highest drying rate compared to the only hot air or only infrared drying method. The fastest drying time was 345 min at a treatment temperature of 90°C, air velocity of 3 m/s, and the greatest drying rate was 0.429 gr/min at a temperature of 80°C, air velocity of 3 m/s. Additionally, the combined infrared hot air method produces a more uniform temperature distribution on the wood surface and lower specific energy consumption, specifically 1027.15 MJ/kg. Keywords: Drying, Hot air, Infrared, Temperature.